Are Funder Open Access Platforms a Good Idea?. (November 2018) - Ross-Hellauer, Tony; Schmidt, Birgit; Kramer, Bianca
As open access (OA) to publications continues to gather momentum, we should continuously question whether it is moving in the right direction. A novel intervention in this space is the creation of OA publishing platforms commissioned by funding organizations. Examples include those of the Wellcome Trust and the Gates Foundation, as well as recently announced initiatives from public funders like the European Commission and the Irish Health Research Board. As the number of such platforms increases, it becomes urgently necessary to assess in which ways, for better or worse, this emergent phenomenon complements or disrupts the scholarly communications landscape. This article examines ethical, organizational, and economic strengths and weaknesses of such platforms, as well as usage and uptake to date, to scope the opportunities and threats presented by funder OA platforms in the ongoing transition to OA. The article is broadly supportive of the aims and current implementations of such platforms, finding them a novel intervention which stands to help increase OA uptake, control costs of OA, lower administrative burden on researchers, and demonstrate funders' commitment to fostering open practices. However, the article identifies key areas of concern about the potential for unintended consequences, including the appearance of conflicts of interest, difficulties of scale, potential lock-in, and issues of the branding of research. The article ends with key recommendations for future consideration which include a focus on open scholarly infrastructure.